Association between sedentary time and plasma leptin levels in middle-aged and older adult population in Taiwan: A community-based, cross-sectional study - Shih, Yu-Lin; Shih, Yun-Hsiang; Huang, Tzu-Cheng; Shih, Chin-Chuan; Chen, Jau-Yuan (Frontiers in Cardiovascular Medicine, 2023)
Background Association of sedentary behavior and plasma leptin levels is a popular topic in recent research. Aged populations often suffer from cardiometabolic diseases, and leptin is considered a novel marker for many cardiometabolic diseases. To further explore this topic, our research investigates the relationship between sedentary time and serum leptin levels in middle-aged and older populations. Methods A total of 396 middle-aged and older adult Taiwanese participants were included in this study. We recorded their self-reported sitting time as sedentary time. Participants were categorized into low leptin, medium leptin group, and high leptin groups according to the tertile of serum leptin level in the study. We also analyzed the anthropometric and cardiometabolic parameters between the three groups. Spearman’s correlation coefficient was used to analyze the correlation between leptin level, sedentary time, and other cardiometabolic risk factors. The relationsip between leptin and sedentary time was also shown in a scatter plot. Multivariate linear regression was performed to determine the association between serum leptin levels and sedentary time after adjusting for age, sex, alcohol consumption, smoking, triglycerides, BMI, fasting plasma glucose, systolic blood pressure, uric acid, creatinine, and ALT. Results In our study, data from a total of 396 participants were analyzed. The average age of participants was 64.75 (±8.75) years, and approximately 41.4% were male. A longer period of sedentary time was observed in the high leptin group. A positive correlation was found between serum leptin level and sedentary time in Spearman’s correlation, in all BMI groups. Serum leptin levels were positively associated with sedentary time in the multivariate linear regression after adjusting for age, sex, alcohol consumption, smoking, triglycerides, BMI, fasting plasma glucose, systolic blood pressure, uric acid, creatinine, and ALT. Conclusion Prolonged sedentary time can be an independent risk factor for high serum leptin levels, and high leptin levels can be a novel marker in future healthcare to screen the individual with prolonged sedentary time. Furthermore, based on our study, future research can further explore the relationship between leptin levels and health promotion, especially decreasing sedentary time in the middle-aged and elder population, which is vulnerable to cardiometabolic diseases.